Faktor risiko sarapan pagi dan makanan selingan terhadap kejadian overweight pada remaja sekolah menengah atas - Shelly Festilia Agusanty; Istiti Kandarina; I Made Alit Gunawan (Jurnal Gizi Klinik Indonesia, 2014)
Background: Overweight or obesity during childhood and adolescence are important risk factors for the presence of adult overweight or obesity. Eating habits in childhood and adolescence influence their healthy condition. Prospective studies of breakfast habits and nutritional status suggest an inverse (protective) association between the frequency of eating breakfast and the risk for overweight and obesity and relationships between no breakfast and increasing body weight.Objective: To examine risk factor of breakfast and snacking related to overweight status in adolescents.Method: This was the observational study with case control design. The first step of the study was screening to have a prevalence of overweight in adolescents. The second step was case control study participated by 100 overweight adolescents and 100 normal weight adolescents in senior high school matched in sex, age, and school. Data collected were weight and height measurements for nutritional status, respondent identity and characteristic, breakfast dan snacking habits and physical activity. Statistical analysis used Chi-Square statistics and multivariable logistic regression analysis.Results: Prevalence of overweight in adolescents were 16,8%. There was significant association between breakfast with overweight (p<0,05; OR=3.1; 95% CI=1.4-7.47). There was no association between snacking and overweight, but there was significant association between frequency of snacking (OR=1.9; 95% CI=1.05-3.50), the energy of snacking (OR=2.1; 95% CI=1.13-4.02), and carbohydrate of snacking (OR=4.5; 95% CI=1.94-11.50) with overweight. In the multivariate model, breakfast habits, carbohydrate of snacking and physical activity had a significant association with overweight.Conclusion: Skipping breakfast was a risk factor for overweight in adolescence. Adolescents who had to snack more than twice a day were having the greater risk factor for overweight.